Evaluation of Land Capability and Land Use Direction In the Krueng Peusangan Hilir Sub-watershed, Bireuen Regency - Halim Akbar; Sarifuddin Sarifuddin; Sakral Hasby Puarada (Aceh International Journal of Science and Technology, 2023)
The destruction of forests in watershed areas has now become a concern of many parties, resulting in floods, landslides, and droughts that continue to increase. Watershed damage is accelerated by increased utilization of natural resources due to population growth and economic development, conflicts of interest, and lack of integration between sectors between the upstream-middle-downstream areas. For this reason, it is necessary to assess land capability in a watershed so that land development follows the land capability class. The research was carried out in the Krueng Peusangan Hilir Sub-watershed, Bireuen Regency, Aceh, Indonesia, from October 2021 to February 2022, which is geographically located at 95°58''00” - 96°52''00” East Longitude and 5°06''00- 5°17 ''00" North Latitude. Land use in the study is dominated by dry land agriculture, covering an area of 19,100.28 ha with a topography area from  0-8% to 25-40%. A survey method by analyzing land capability classes at the study site was carried out for each land map unit (LMU) by comparing land conditions with the land capability evaluation Hockensmith and Steele’s criteria (overlaid of determined thematic maps). The result shows that soil erodibility decreased linearly with increasing organic matter in the soil. Soils with high organic matter content have high erodibility. For the limiting factor on slopes in land capability classes found in  II, III, IV, and VI class categories that are found in all LMUs, if these LMUs are used for agricultural cultivation, soil conservation measures are needed, such as making mound terraces or canal mound terraces, planting in strips and using mulch. The results show that the land capability classes consisted of 16668.30 ha in the land capability II class, 4184.06 ha land capability in the III class, 4524.91 ha in the land capability IV class, and 190.79 ha land capability VI class with a factor inhibiting soil erodibility (medium – very high) and slopes (wavy - rather steep)